Group Investigation in Music Instruction: A Pedagogical Scenario - Andrews, Bernard (Canadian University Music Review / Revue de musique des universités canadiennes, 1993)
Group investigation is a teaching strategy that requires students to work in small groups and solve problems by reaching a consensus or solution. Involvement in the investigative process enables a teacher to provide an environment which alleviates conflict and facilitates cooperation. Further, the quality of the solution is higher when reached through consensus. The students are positively motivated to learn and behavioral skills are expanded.In this paper, the writer examines the history and effectiveness of group investigation since its inception as a teaching strategy by Herbert Thelen. Based upon this analysis and upon formative trials in varied classroom settings, he postulates how the strategy can be utilized by music educators in school and university settings.